If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r + 6 = 22 Reorder the terms: 6 + 4r = 22 Solving 6 + 4r = 22 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4r = 22 + -6 Combine like terms: 6 + -6 = 0 0 + 4r = 22 + -6 4r = 22 + -6 Combine like terms: 22 + -6 = 16 4r = 16 Divide each side by '4'. r = 4 Simplifying r = 4
| e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x | | 5x+13=-39-8x | | 114-2x=9x+18 | | 4x+7y=299 | | 16x-8=6x+42 | | 13x+13=76-4x | | 34-g=25 | | 18x-9=6x+42 | | 9-9x=144-44x | | 2x+38=10x-26 | | -72-10x=9x+18 | | 2x+38=10-34 | | 2x^2-2x+1=0.55 | | x+4=-7+2x | | 11x-16=116 | | 4t-6=14 | | 14x+7=30x |